Comparison of clinico-pathological characteristics and survival of recurrent ovarian cancer patients on seven different chemo-protocols - Sattar Saima; Ahmad Mobasher; Saeed Hamid; Saleem Zikria; Danish Zeeshan; Akhlaq Muhammad (Acta Pharmaceutica)
Despite growing prevalence of ovarian cancer (OC) in Pakistan, no literature evidence exists regarding its clinic-pathological characteristics, survival and compliance of patients with recurrent ovarian cancer on various chemo-protocols. An observational study was conducted by enrolling 251 recurrent OC patients on 7 different chemo-protocols, from a specialized cancer care hospital, Lahore, Pakistan, using convenient judgmental sampling. The study was conducted for a period of 6 months. Most of the patients were between 18 and 70 years of age, with IIIC FIGO stage and papillary serous histological grade. As per RECIST, improved partial response (PR) (63.3 %) and complete response (CR) (52.1 %) was observed in the CP (carboplatin + paclitaxel) arm, substantiated by improved median progression free survival (PFS) and overall survival (OS) in CP and CD (carboplatin + docetaxel) arms, respectively, yet with no significant differences in survival curves, PFS (p = 0.12) and OS (p = 0.22). Interestingly, the highest and the lowest patient non-compliance were observed in CG (carboplatin + gemcitabine) (81.6 %) and paclitaxel (4.5 %) arms, resp. As per the hazard model for survival, topotecan showed significant association with the therapy related events/deaths compared to other protocols. These data suggest that CP regimen exhibited improved clinical efficacy and decreased toxicity related non-compliance in recurrent ovarian cancer patients of Lahore.